Hibernasi UU Desa di Kawasan Perkebunan Sawit Berskala Besar: Studi Kasus Ekspansi Sawit di Kabupaten Sintang, Kalimantan Barat - Kharis Fadlan Borni Kurniawan; Arya Hadi Dharmawan; Titik Sumarti; Mochammad Maksum (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2023)
This paper seeks to present the results of testing the implementation of the Village Law in villages covered by large-scale oil palm plantations. The socio-economic and political dynamics of villages with oil palm are in stark contrast to villages that are relatively free from the circle of the plantation capitalist system. This research examines it by focusing on the study of customary land acquisition practices and partnerships between smallholders and oil palm plantation companies in the Sintang District. Qualitative research using a case study approach which is the basis for writing this paper found that the Village Law, which many people hoped would free villages from the threats of the industrialization of forests and oil palm plantations, in fact, could not do much or, in the author's language, the Village Law was in hibernation.